Effects of Feeding Fat During Pregnancy and Lactation on Growth Performance, Milk Composition and Very Low Density Lipoprotein Composition in Rats - Chwen, Loh Teck; Ling, Foo Hooi; Abdul Wahab, Zurina; Koon, Tan Bee (Nutrition Society of Malaysia, 2002)
The effects of dietary fat during pregnancy and lactation on growth performance of pups, milk composition and very low density lipoprotein composition in rats were studied. A total of 33 dams were used in this study and each litter was adjusted to 8 pups per dam. The dams were fed on high fat (150 g fat/kg diet, HF), medium fat (75 g fat/kg of diet, MF) and low fat (2.5 g fat/kg diet, LF) diets. The body weights of dams increased during pregnancy and decreased after pregnancy. The HF pups had a higher body weight and higher weight gain than those of LF pups. The amount of feed intake of HF dams was significantly higher than LF and MF dams. The HF dams had significantly higher milk fat and water concentrations than LF dams. The milk protein was not significantly different among the treatment groups. All dams showed hypertriacylglycerolaemia in their very low density lipoprotein (VLDL) in late pregnancy. The VLDL-protein concentrations increased during the first week after parturition. The HF dams showed a greater response to the dietary fat than that of LF and MF dams. The findings suggest that addition of fat in the diet during pregnancy and lactation may improve the milk quality through modifying the composition of VLDL contents, leading to better growth of pups.